CD20 is dispensable for B-cell receptor signaling but is required for proper actin polymerization, adhesion and migration of malignant B cells - Kozlova, Veronika; Ledererova, Aneta; Ladungova, Adriana; Peschelova, Helena; Janovska, Pavlina; Slusarczyk, Aleksander; Domagala, Joanna; Kopcil, Pavel; Vakulova, Viera; Oppelt, Jan; Bryja, Vitezslav; Doubek, Michael; et al. (PLoS One, 2020)
Surface protein CD20 serves as the critical target of immunotherapy in various B-cell malignancies for decades, however its biological function and regulation remain largely elusive. Better understanding of CD20 function may help to design improved rational therapies to prevent development of resistance. Using CRISPR/Cas9 technique, we have abrogated CD20 expression in five different malignant B-cell lines. We show that CD20 deletion has no effect upon B-cell receptor signaling or calcium flux. Also B-cell survival and proliferation is unaffected in the absence of CD20. On the contrary, we found a strong defect in actin cytoskeleton polymerization and, consequently, defective cell adhesion and migration in response to homeostatic chemokines SDF1α, CCL19 and CCL21. Mechanistically, we could identify a reduction in chemokine-triggered PYK2 activation, a calcium-activated signaling protein involved in activation of MAP kinases and cytoskeleton regulation. These cellular defects in consequence result in a severely disturbed homing of B cells in vivo.
Keywords: antigeny CD20; multimerizace proteinu; Actins; Cell Line, Tumor; polymerizace; Mice, SCID; Antigens, CD20; receptory antigenů B-buněk; signální transdukce; Lymphoma, B-Cell; Leukemia, B-Cell; B-lymfocyty; B-buněčný lymfom; Receptors, Antigen, B-Cell; aktiny; Signal Transduction; buněčná adheze; Cell Movement; myši inbrední NOD; Protein Multimerization; Animals; lidé; myši transgenní; Gene Knockdown Techniques; Humans; zvířata; myši SCID; Polymerization; pohyb buněk; myši; B-Lymphocytes; genový knockdown; nádorové buněčné linie; Mice; Mice, Inbred NOD; Mice, Transgenic; Cell Adhesion; leukemie B-buněčná